Analisis Pengaruh Budaya, Pemberdayaan, dan Komitmen Organisasional dalam Meningkatkan Kinerja Pegawai pada Sekretariat DPRD Kabupaten OKU - Maradona, Irfan; Efriati, Rini; Oktarina, Yetty; Sari, Yunita (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The aim of this research is to examine how culture, organizational commitment and empowerment of the OKU Regency DPRD Secretariat influence employee performance. This research is descriptive in nature and uses quantitative and associative methods in the sampling process. The sampling technique was random, totaling 57 people, including employees of the DPRD Secretariat of Ogan Komering Ulu Regency, which is the population in this study. This research uses multiple linear regression to test variables that are thought to influence improving employee performance at the OKU Regency DPRD Secretariat. The results of this research show that simultaneously there is a positive and significant influence between the variables of organizational culture, empowerment and commitment on employee performance variables at the Ogan Komering Ulu Regency DPRD Secretariat, but partially only organizational culture does not have a significant effect on employee performance at the Ogan Regency DPRD Secretariat. Komering Ulu.